Diques clásticos na formação corumbataí (p) no nordeste da bacia do paraná, SP: Análise sistemática e significações estratigráficas, sedimentológicas e tectônicas - Perinotto, José Alexandre de Jesus [UNESP] (2008)
This paper aims to present the results of systematic survey on clastic dykes in the Corumbataí Formation (Permian), in the northeast region of the State of São Paulo. Besides this, the paper analyses genetic aspects of those features as well as their stratigraphic and sedimentologic implications in terms of geologic evolution of the northeastern Paraná Sedimentary Basin during Permian times. The field works had been developed in 3 main Corumbataí Formation outcrops (2 road cuts and a quarry) supposed to show the most important clastic dikes occurrences in the studied area. Basically, the sedimentary intrusions are formed by fine sand or silt size particles and had penetrated host rocks as near-vertical, centimeter thick, dykes (most common form) or as horizontal sheets, forming clastic sills (subsidiary form), both with variable geometric forms and dimensions. A lot of dyke walls show undulations suggesting pre-diagenetic clastic intrusions, probably near the ancient depositional surface. Almost all intrusions occur in the superior third portion of the Corumbataí Formation and some similar features seem to appear in the adjoining superposed Pirambóia Formation base. In this article the authors defend a seismic origin hypothesis for the clastic intrusions. It is important to mention that clastic intrusions tend to occur linked to expressive seismic events, with magnitude upper to 5. The analysis of isopach maps of the Permian and Mesozoic units of the Paraná Sedimentary Basin in the study area suggests a depositional system changing, from epicontinental sea conditions to shallow platform and, finally, to coastal deserts. Probably, this environmental change was driven by regional uplift accompanied by seismic events. It is possible that ancient seismicity triggered liquefaction processes and the resulting clastic intrusions. In this sense, those clastic features might be properly namedseismites.